The role of a future lawyer in an Artificial intelligence environment - Dasanayaka, Chathura Gayan (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Around the world, companies, governments and universities are inventing Artificial Intelligence without thinking about its legal and regulatory threats. As its impact becomes increasingly ubiquitous, opening a portal to new opportunities, efficiency and connectivity for lawyers, judges and litigants Artificial Intelligence related data analytics has also unleashed a labyrinth of growing concerns which affect the justice system and rule of law. Therefore, this research Paper intends to examine potential of Artificial intelligence in enhancing access to justice and the difficulties associated with its implementation. In such a context the objective of this research is to analyze How can artificial intelligence be used to improve the access to justice based on the role of a future lawyer in an Artificial intelligence environment.